2017 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--27954
|View full text |Cite
|
Sign up to set email alerts
|

Board # 91 : The Influence of Gender Grouping on Female Students' Academic Engagement and Achievement in Engineering and Biology: A Case of Small Group Work in Design-based Learning (Work in Progress)

Abstract: Her research focuses on the relationship between motivation, affects and learning associated with K-16 science concepts and various instructional contexts (e.g., small groups, project-based learning) utilizing mixed-methods approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Not all papers found within the structured literature search focus explicitly on DBL, and thus, they do not all mention it as such. Some studies (e.g., Apedoe et al 2008;Reynolds et al 2009;Bagiati et al 2010;Carroll et al 2010;Guo et al 2016;Lacy 2016;Guo et al 2017;Neve and Keith-Marsoun 2017;Zhang et al 2018Zhang et al , 2019 did mention DBL explicitly. While others (Chu et al 2017;Vongkulluksn et al 2018;Chan and Holbert 2019) mentioned makerspace and maker activities that suggest a specific type of DBL, emphasizing the essence of making in constructive learning.…”
Section: Design-based Learningmentioning
confidence: 99%
See 4 more Smart Citations
“…Not all papers found within the structured literature search focus explicitly on DBL, and thus, they do not all mention it as such. Some studies (e.g., Apedoe et al 2008;Reynolds et al 2009;Bagiati et al 2010;Carroll et al 2010;Guo et al 2016;Lacy 2016;Guo et al 2017;Neve and Keith-Marsoun 2017;Zhang et al 2018Zhang et al , 2019 did mention DBL explicitly. While others (Chu et al 2017;Vongkulluksn et al 2018;Chan and Holbert 2019) mentioned makerspace and maker activities that suggest a specific type of DBL, emphasizing the essence of making in constructive learning.…”
Section: Design-based Learningmentioning
confidence: 99%
“…Some studies (Giannakos and Jaccheri 2013;Giannakos et al 2014;Guo et al 2016Guo et al , 2017 reported on evaluations involving female students. Two studies (Giannakos and Jaccheri 2013;Giannakos et al 2014) presented an evaluation with a total of 37 girls who were involved in a DBL workshop, measuring their emotions and intentions to participate in DBL in future.…”
Section: Student Population Samplementioning
confidence: 99%
See 3 more Smart Citations